Ret transgenic mouse model of spontaneous skin melanoma: focus on regulatory T cells - Umansky, Viktor; Sevko, Alexandra (Pigment cell & melanoma research, 2013)
Ret transgenic mouse model of skin malignant melanoma is characterized by the overexpression of the human ret transgene in melanin-containing cells. Transgenic mice spontaneously develop skin tumors with metastases in lymph nodes, lungs, liver, brain, and the bone marrow. Tumor lesions show typical melanoma morphology and express melanoma-associated antigens. Although transgenic mice demonstrate an accumulation of melanoma antigen-specific memory and effector T cells, their anti-tumor effects could be blocked by highly immunosuppressive leukocytes enriched in the tumor microenvironment and in the periphery. Here, we discuss the role of one of the most potent immunosuppressive subset, regulatory T cells, in the melanoma progression in this model.
Gesehen am 17.02.2022